The Effect of Contextual Teaching and Learning Model through Writing Poetry Ability in Eight Grade Students of SMP Negeri 2 Garoga in Academic Year 2018/2019 - Situmorang, Erlinawati; Saragih, Mariatih (International Journal of English Literature and Social Sciences (IJELS), 2019)
This study dealt with the The Effect of Contextual Teaching and Learning Model through Writing Poetry Ability in Eight Grade Students of SMP Negeri 2 Garoga in Academic Year 2018/2019. The aims of this study are a) to determine the average poetry writing ability in Eight grade students of SMP Negeri 2 Garoga Academic Year 2018/2019 using the Contextual Teaching and Learning learning model.b) To determine the average ability to write poetry by eighth grade students of SMP Negeri 2 Garoga Academic Year in 2018/2019 with expository methods.c) To explain the effect of using the Contextual Teaching and Learning learning model ability to write poetry by eighth grade students of SMP Negeri 2 Garoga Academic Year 2018/2019. The Result of the average value of student learning outcomes in eight grade students of SMPN 2 garoga to write poetry before getting benefits is 68.79 (good enough). 77.06 (Good) Model of Teaching and Contextual Teaching have a significant (positive) influence on the ability to write texts by eighth grade students of SMPN 2 Garoga in Academic 2018/2019 with the hypothesis that t_(0>) t_tabel is 3,59 > 2,05 proven that the alternative hypothesis (H_a) is accepted.